Engaging transculturality: concepts, key terms, case studies - Abu-Er-Rub, Laila; Brosius, Christiane; Meurer, Sebastian; Panagiotopoulos, Diamantis; Richter, Susan (Routledge, 2019)
"Engaging Transculturality is an extensive and comprehensive survey of the rapidly developing field of transcultural studies. In this volume, the reflections of a large and interdisciplinary array of scholars have been brought together to provide an extensive source of regional and trans-regional competencies, and a systematic and critical discussion of the field's central methodological concepts and terms"--
Includes bibliographical references and index
Keywords: Europa; Asien; Aufsatzsammlung